AtINO80 and AtARP5 physically interact and play common as well as distinct roles in regulating plant growth and development. Issue 1 (3rd April 2019) - Kang, Huijia; Zhang, Chi; An, Zengxuan; Shen, Wen‐Hui; Zhu, Yan
Summary: The proper modulation of chromatin structure is dependent on the activities of chromatin‐remodeling factors and their interplays. Here, we show that the Arabidopsis chromatin‐remodeler AtINO80 interacts with the actin‐related protein AtARP5 and can form a larger protein complex. Genetic analysis demonstrated that AtARP5 acts in concert with AtINO80 during plant cellular proliferation and replication stress response. At the same time, AtARP5 is not required for AtINO80 ‐mediated control of flowering time and related transcriptional regulation, and their chromatin distribution patterns on regions of flowering‐repressor genes FLC/MAF4/MAF5 are also different. An in vitro DNase I digestion assay revealed that the AtINO80N‐terminus can weakly bind DNA, an interaction that is significantly inhibited by H2A.Z/H2B addition. AtARP6, a specific subunit of SWR1‐C that mediates the H2A.Z exchange, was found to have a previously unexpected inhibitory role in the local chromatin enrichment of AtINO80. Further genetic analyses revealed the functional interplay between AtINO80 and AtARP6 and their critical roles in embryogenesis and post‐embryonic organ development, as well as the synergy of AtARP5 and AtARP6 in maintaining genomic stability. Our findings provide insights into the common and distinct roles of AtINO80 and AtARP5 in diverse aspects of plant development.